To honor and trust eaudiobook Bridal veil island series, book 3. - Peterson, Tracie (Bridal Veil Island, 2013)
To the delight of listeners everywhere, best-selling authors Tracie Peterson and Judith Miller have teamed up to craft compelling inspirational tales. Here, as governess Callie DeBoyer arrives at Bridal Veil Island with her employers, she faces a difficult decision. Her missionary parents are desperate to have her join them in Africa, but Callie wonders if her thoughts of leaving are because God is calling her - or because she wants to escape her painful personal life.